Diterpenoid alkaloids of Delphinium buschianum GROSSH. - BİTİŞ, LEYLA (WILEY-V C H VERLAG GMBH, 2007)
From the aerial parts of Delphinium buschianum GROSSH., collected in Turkey, a new diterpenoid alkaloid 1, named budelphine, was isolated along with the known diterpenoid alkaloids karakoline (2), 18-hydroxy-14-O-methylgadesine (3), delsoline (4), lapaconidine (5), columbianine (6), 14-benzoylneoline (7), and hetisine (9). ne structure of 1 was established on the basis of H-1-, C-13-, DEPT, H-1,H-1-COSY, NOESY, HSQC, and HMBC NMR studies.
Keywords: C-19-DITERPENOID ALKALOIDS; C19-DITERPENOID ALKALOIDS; NORDITERPENOID ALKALOIDS; CHEMISTRY; CHINA